Proyecto de factibilidad para la implementación de una distribuidora y comercializadora de balanceados para ganado vacuno lechero, en el cantón Centinela del Cóndor, provincia de Zamora Chinchipe - Viñan Soto, Yasmin Milenia (2015)
This investment project is done to determine the "PROJECT FEASIBILITY FOR THE IMPLEMENTATION OF A distributor and marketer of feed for dairy herds in the Canton Centinela del Condor, Zamora Chinchipe province," it was necessary to approach four specific objectives which were developed as follows: The study yielded information on the potential market demand, which was 569 for year one; the actual demand of 445, with an average use of 47 times giving a total real demand for 20993 year 17977 and effective, just as supply was identified giving an annual total of 6816, 28% projected growth rate dairy livestock sector, which showed that there is an unmet demand for 9253 for year one and 24837 for year five, results favoring the project in question. The technical study unveiled the installed capacity will be 7923 per year and capacity utilization 3962 to 7923 year one and year five, the macro and micro location is also indicated by weighting the result of 7.97, it showed that the optimum place for the implementation of the project is the city center; project engineering, showed processes, distribution and implements necessary for the proper conduct of business. The administrative structure possible to design the structural, functional and positional organization, just as the manual functions are developed, the trade name of the company, which was limited liability company, with a duration of 5 years of life was established, and permissions required for proper operation is defined. In the financial study the total initial investment is $ 53,076.99, consisting of $ 36,440.57 fixed assets is met; Deferred capital of $ 1,748.25 and 14,888.18 monthly duty, whose investment will be financed with 60% equity and 40% with loan Cooperative Manuel Esteban Godoy with a lending rate of 19.90%. Total costs were $ 177,787.33 and 234,679.27 income for year one are set. The financial evaluation found positive cash flows for the project is so for the first year were $ 43,339.15 and for the year 5 $ 53,091.27; financial indicators were calculated with a discount rate of 19.90% giving a NPV of $ 84,357.46; the internal rate of return of 79.76% over the opportunity cost of capital; benefit cost ratio of 1.32, indicating that for every dollar invested will get $ 0.32 of profit; Capital recovery will be in one year, seven months and approximately 13 days; and sensitivity analyzes with increased costs and reduced income yielded 0.99 in both periods it is shown that the project is feasible. Finally, with the results found by applying the appropriate techniques, it showed that the project is viable, because positive balances are obtained, which considered feasible its implementation, and this new company will contribute to economic and productivity growth in the canton Sentinel Condor